Impacts of cybersecurity threats on construction stakeholders in Malaysia amidst industrial revolution 4.0 / Ramli Isa, Har Einur Azrin Baharuddin and Airul Faizal Othman - Isa, Ramli; Azrin Baharuddin, Har Einur; Airul Faizal Othman, Airul Faizal Othman (UiTM Press, 2024)
Cybersecurity is one of the elements of IR 4.0 which is created to provide security and protect digital information which includes construction industry from expose to cybersecurity threat. Cyberthreats happen to any digital device and working in digitalisation environment, files will be shared online, everyone can access those files if it does not provide a security password to open it. There are ways to overcome and minimise cybersecurity threats which need to be explored to avoid threats. Thus, the aim is to explore the impacts of the cybersecurity threats among stakeholders in construction in IR 4.0. The objectives are to identify the potential threats of cybersecurity on construction stakeholders in Malaysia, followed by recommendation ways to improve the implementation of cybersecurity usage among stakeholders and minimise threats incidents for safety purposes for construction stakeholders’ company. The data obtained using quantitative method where the random sampling survey conducted through distribution of questionnaire to stakeholders in construction. Findings show that, cybersecurity systems in construction are not very deep because currently the construction sector is not a major contributor in cyber security intrusions and threats. Stakeholders in construction implement cybersecurity measures such as use of anti-virus, regular software update etc., which most of these are related to their task where all work is now completed using digitalised gadget. In terms of ways to improve the implementation of cybersecurity usage among stakeholders and minimise threats incidents, it can be concluded that individual approach is the most effective way medium to overcome this problem.